GENDER, EDUCATION AND POPULATIONS IN SITUATIONS OF SOCIAL VULNERABILITY AND THEIR ASPECTS OF HEALTH PROMOTION - Nelson Martins Júnior, Leonidas; da Silva Santos, Juliana; Ximenes Oliveira, Silvia; Trindade Benites, Patrícia; Kayan de Oliveira Nascimento, Lucas; Corrêa Bezerra de Araújo , Renata (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to analyze, through a narrative literature review, the interfaces between gender, education, and health promotion aimed at populations in situations of social vulnerability. The research was based on studies published between 2012 and 2023, encompassing educational experiences and public policies that address social determinants of health. The analysis revealed two main categories: (1) health education as an instrument of citizenship and resistance and (2) the invisibility of social markers and the limitations of public policies. The results indicate that educational practices guided by listening, territory, and intersectionality can strengthen the protagonism of marginalized subjects, expanding their access to rights and social participation. However, the persistence of biomedical approaches, intersectoral fragmentation, and the low critical training of professionals still limit the effectiveness of affirmative action policies. It is concluded that health promotion in contexts of inequality requires educational practices committed to social justice, equity, and the recognition of diversity.